Forest management and FSC certification: a systematic review - Fagundes, Camila; Schreiber, Dusan; Nunes, Moema Pereira; Fernandes, Maria Eduarda (Revista de Administração da UFSM, 2024)
Objective and Methodology: Many studies have been published since the creation of the Forest Stewardship Council (FSC) to better understand this certification. Through a systematic review of the literature in 2022, this article aims to identify business entities motivations, benefits, and challenges of FSC certification. Through the definition of some inclusion criteria (Scientific Articles; Specific subject areas; FSC, or Forest Stewardship Council, appears in the title, abstract, and/or keywords; FSC means “Forest Stewardship Council”; FSC benefits and challenges), this study reviews a total of 74 publications from 2005 to 2022 from five different data bases (Scopus, Science Direct, Wiley Online Library; Springer Link; Web of Science). More than one author helped with the selection of papers to remove the risk of bias. Results: As main results, the motivations for deployments of the FSC certification are linked to economic issues as well as potential benefits. However, FSC still has several challenges to overcome, such as: high cost, lack of price premium, investment return, and financial dependency in the case of small producers. Social benefits and challenges were also mapped. Such results are directly linked to the type of methodology used in each paper. Originality: As a conclusion, many field studies still need to be developed due to the superiority of documentary research based on audit reports. Although this kind of document has several advantages, some disadvantages are also detected. This paper provides an overview of the FSC directing future research interested in the theme.